2011
DOI: 10.2478/s11687-011-0025-3
|View full text |Cite
|
Sign up to set email alerts
|

Endoparasite community of Rattus norvegicus captured in a shantytown of Buenos Aires City, Argentina

Abstract: SummaryThe aim of this study was to evaluate the role of the brown rat (Rattus norvegicus) as a potential reservoir of zoonotic parasites in an urban area of Argentina. A parasitological survey in 40 brown rats trapped in a shantytown of Buenos Aires City was carried out. 97.5 % of the analyzed rats were parasitized with at least one of the 12 species of helminth or protozoan species recorded. Among the species identified, Hymenolepis nana is recognized as one of the most common human helminthes parasites. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
33
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 42 publications
9
33
1
6
Order By: Relevance
“…Moreover, previous studies have shown that nematodes and cestodes are more abundant in helminth communities of R. norvegicus (Abu-Madi et al, 2001Hancke et al, 2011;Kataranovski et al, 2011). This result is consistent with our findings, as nematodes accounted for 98.7% of the helminth community.…”
Section: Discussionsupporting
confidence: 96%
“…Moreover, previous studies have shown that nematodes and cestodes are more abundant in helminth communities of R. norvegicus (Abu-Madi et al, 2001Hancke et al, 2011;Kataranovski et al, 2011). This result is consistent with our findings, as nematodes accounted for 98.7% of the helminth community.…”
Section: Discussionsupporting
confidence: 96%
“…The success of murine rodents in anthropogenic habitats could be the reason for many parasitological studies done worldwide. In general, studies have focused primarily on list of all parasites species and analyzed biotic and abiotic factors influencing composition and parasite burden (see Battersby et al 2002;Milazzo et al 2010;Easterbrook et al 2007;Kataranovski et al 2008Kataranovski et al , 2011Hancke et al 2011). In recent decades, the detection of diseases associated with rodents as reservoirs has increased (see Meerburg et al 2009), which gives them a significant role in disease transmission to humans.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, these rodent species are not only potential disease reservoirs since in these shantytowns they are actually carrying several pathogens that produce diseases to humans, such as Leptospira spp. (Seijo et al 2002), hantavirus Seoul (Cueto et al 2008), and human helminth parasites (Hancke et al 2011). This scenario, in association with other socio-environmental vulnerabilities, as poor public services, would increase the effect of these zoonoses within shantytowns.…”
Section: Discussionmentioning
confidence: 97%